Domain-adapted discovery of PET depolymerisation routes using in-house curated scientific literature - Sivan, Dawn; Zafar, Saima; Kumar, K. Satheesh; Manoj Kumar, T. K.; Moorthy, Kohbalan; Izan Izwan, Misnon; Yang, Chun-Chen; Jose, Rajan (Royal Society of Chemistry, 2026)
Curated chemical literature combined with a domain-adapted language model is shown to generate experimentally feasible PET depolymerisation pathways. This work establishes a practical data-guided approach for evaluating and discovering viable routes in plastic waste management.